The double burden of stressful life events among professional nurses: public mass shootings during the COVID-19 pandemic - Ek-Uma Imkome (International Journal of Qualitative Studies on Health & Well-Being)
Background This study explores nurses’ experiences amid the dual challenges of the COVID-19 pandemic and public mass shootings, highlighting the emotional and professional strains they faced while providing care in crisis situations. Methods This qualitative study used semi-structured, in-depth interviews with a sample of 16 nurses caring for patients who were either injured during a public mass shooting or were infected with COVID-19. The participants were selected through purposeful sampling. Thematic analysis was undertaken, and themes derived from structural understanding illuminated nurses’ perceptions of patient care during the COVID-19 pandemic. Results Qualitative data analysis revealed five main themes: stressful life events, flashbulb memories, service-oriented mindsets, team collaboration keys, and professional needs. The theoretical interpretation points to multidimensional perceptions of nurses and the need to confirm these perceptions and reconcile them with the psychological impact of stressful life events, making future adjustments and adaptations possible. These results build upon our previous work, first presented as a preprint, which highlighted initial themes and set the foundation for this expanded analysis. Conclusions The study underscores how crises impact nurses’ perceptions, highlighting the need for improved support, teamwork, and ongoing training to address their psychological needs during emergencies.